Left ventricular assessment in patients with mucopolysaccharidosis using conventional echocardiography and myocardial deformation by two-dimensional speckle-tracking method - Mirela F.A. Andrade; Isabel Cristina B. Guimarães; Angelina X. Acosta; Emília Katiane E.A. Leão; Moisés I.G. Moreira; Carlos Maurício C. Mendes (Elsevier, 2019)
Objective: Mucopolysaccharidosis is a rare genetic disease characterized by the intralysosomal deposition of glycosaminoglycans. Cardiovascular impairment is a common feature. Cardiac signs and symptoms are underestimated due to the disease involvement in other organs. Enzyme replacement therapy can be used in mucopolysaccharidosis I, II, IV, and VI. Thus, the knowledge about the use of new echocardiography tools is relevant to improve the care of this population. This study aimed to describe left ventricular function assessment by conventional echocardiography and left ventricular global longitudinal strain analysis and compare the alterations in patients receiving enzyme replacement therapy and who had different ages at the start of therapy. Method: Outpatient-based descriptive study. The patients were submitted to conventional echocardiography and left ventricular global longitudinal strain measurement. Results: Sixteen patients were evaluated; median age of 14.2 years (SD = 5.2 years). Left ventricular hypertrophy was found in nine patients (56.2%). All patients had preserved left ventricular systolic function (Simpson and Teichholz). Nine (56.2%) patients showed alterations in left ventricular global longitudinal strain. The study showed a positive association between left ventricular hypertrophy and alteration in the left ventricular global longitudinal strain, and late start of enzyme replacement therapy and alteration in the left ventricular global longitudinal strain. Conclusion: Echocardiographic alterations in patients with mucopolysaccharidosis were frequently observed, especially alterations in the left ventricular geometry and subclinical dysfunction. Patients who had a late enzyme replacement therapy start showed an association with worse left ventricular global longitudinal strain values, reinforcing the need for early diagnosis and treatment. The use of new echocardiographic tools may improve the follow-up of these patients. Resumo: Objetivo: A mucopolissacaridose é uma doença genética rara, caracterizada por depósito intralisossômico de glicosaminoglicanos. O comprometimento cardiovascular é frequente. Sinais e sintomas cardíacos são subestimados pelo envolvimento da doença em outros órgãos. A terapia de reposição enzimática pode ser usada em mucopolissacaridose I, II, IV e VI. Assim, o conhecimento da aplicação de novas ferramentas de ecocardiografia é relevante para melhorar a assistência dessa população. Este estudo visou descrever a função do ventrículo esquerdo pelo ecocardiograma convencional e pela análise do strain global longitudinal do ventrículo esquerdo e comparar as alterações em pacientes que fazem uso da terapia de reposição enzimática e que tiveram idades distintas de início da terapia. Método: Estudo descritivo de base ambulatorial. Os pacientes foram submetidos à ecocardiografia convencional e medida do strain global longitudinal do ventrículo esquerdo. Resultados: Foram avaliados 16 pacientes; mediana de 14,2 anos (desvio: 5,2 anos). Hipertrofia do ventrículo esquerdo foi encontrada em nove pacientes (56,2%). Todos os pacientes tiveram função sistólica do ventrículo esquerdo preservada (Simpson e Teichholz). Nove (56,2%) pacientes apresentaram alteração no strain global longitudinal do ventrículo esquerdo. O estudo mostrou associação positiva entre hipertrofia do ventrículo esquerdo e alteração no strain global longitudinal do ventrículo esquerdo e início tardio da terapia de reposição enzimática e alteração no strain global longitudinal do ventrículo esquerdo. Conclusão: Alterações ecocardiográficas em pacientes com mucopolissacaridose foram frequentes, especialmente alterações na geometria e disfunção subclínica do ventrículo esquerdo. Pacientes que iniciaram tardiamente a terapia de reposição enzimática apresentaram associação com piores valores de strain global longitudinal do ventrículo esquerdo, o que reforça a necessidade do diagnóstico e tratamento precoces. O uso de novas ferramentas de ecocardiografia pode melhorar o acompanhamento desses pacientes. Keywords: Mucopolysaccharidosis, Echocardiography, Cardiac function tests, Enzyme replacement therapy, Palavras-chave: Mucopolissacaridose, Ecocardiografia, Testes de função cardíaca, Terapia de reposição enzimática